Preparation of Activated Carbon from the external shell of Coconut fruit using modified carbonization and chemical thermal activation - Mayada Ali; Qaidar Jarjees; Omar Ramadhan (College of Education for Pure Sciences, 2005)
The research workaimed to prepare an activated carbon from the external shell of the coconut . the coconut shell is rich in lignin and has a high content of carbon .The prepare method involved modification of the carbonization process by addition of different percentages of aniline. Mean while keeping the coconut amount and carbonizing agent (NaOH) in constant ratios, Carbonization was conduced at 550' C for 3 hrs. The product was purified by washing with distilled water , refluxing with 10% HCI , then carbon produced was dried for 24 hrs at 1 10-120'C Evaluation of carbon was carried out through measuring density , humidity and adsorptive properties for external and internal area by inelhylene blue and iodine adsorption respectively.